PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Wahyu Utomo; Rahayu Triastity; Retno Susanti (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the significance effect of experiential marketing on customer satisfaction, analyze the significance effect of experiential marketing and satisfaction on customer loyalty and analyze the significance effect of experiential marketing on customer loyalty with customer satisfaction as an intervening variable. This research is a survey of customers at PT. Nasmoco Slamet Riyadi Solo with a sample of 100 people with purposive sampling technique. The technique of collecting data used questionnaires, observation and documentation. Data analysis used path analysis. The results showed that experiential marketing had a significant effect on customer satisfaction. Experiential marketing has a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Experiential marketing has a significant effect on customer loyalty with customer satisfaction as an intervening variable